Incidentaloma en lactantes de 6 meses de edad - Molina, J.; Martínez, D.; Sagaseta de Ilurdoz, M.; Azanza, M.J.; Chueca, M.; Oyarzábal, M.; de Miguel, C. (Anales del Sistema Sanitario de Navarra, 2009)
Este artículo no tiene resumen.